A comparative study on reasoning strategies in L1 and L2 critical reading-thinking tests - Mohamad Ali, Afiza (IDOSI Publications, 2013)
The need to investigate test-takers’ reading comprehension processes has been emphasized in the related literature. The present study aimed at examining English as a Second Language (L2) students’ reasoning processing strategies in taking critical reading-thinking tests in their first and second language using a think aloud approach. The study is set against a background of recent research into critical thinking and reading comprehension in a second language. Reasoning strategies were identified from the protocol analyses and these were categorized into reasoning formulation, reasoning monitoring and reasoning regulation strategies. The majority strategies indicated that inference acted as an over-arching strategy that linked to the reasoning strategies which made inferences from contextual clues, background knowledge and knowledge of formal schemata. Implications of the findings for pedagogy and future research into critical reading in a second language are considered.